Doppler monitoring of preventive migraine treatment - Kalashnikov, V.; Vastyanov, R.; Stoyanov, O. (Journal of Education, Health and Sport, 2025)
The article presents an analysis of literature data and the results of our own clinical and Doppler examination of 116 young patients with migraine. (18-45 years old), a clinical and neurological examination was performed, an assessment of the intensity of the degree of decrease in the patient's functional activity, a study of the state of cerebral arteries and cerebrovascular reactivity using ultrasound Doppler. Cerebral hemodynamics during a migraine attack is characterized by a pattern vasospasm in migraine without aura and a pattern of impaired perfusion in migraine with aura in the middle cerebral arteries, as well as increased perfusion in the cerebral arteries. Hyperreactivity to hypercapnic load and photoreactivity test is a characteristic Doppler pattern in patients with migraine without aura. Hyperreactivity to hyperventilatory load, reflecting a hyperconstrictive vascular response, predominates in migraine with aura. The use of Topiramate for the preventive treatment of migraine in both clinical groups significantly reduces the frequency, duration and intensity of migraine attacks. Under the influence of the drug, a decrease in the frequency, duration and intensity of attacks was observed. The vascular effect of the drug was manifested in a decrease in the initially increased blood flow velocity in the MCA. The drug contributed to the normalization of cerebrovascular hyperreactivity, mainly to the CO2 test in patients with migraine with aura and to the photoreactivity test in patients with migraine without aura.